Adrenocorticotropic Hormone-Secreting Esthesioneuroblastoma with Ectopic Cushing's Syndrome - Chung, Young Soo (Yonsei Med J, 2020)
Esthesioneuroblastoma as a source of ectopic Cushing's syndrome is rare, and to the best of our knowledge, only 20 cases have been reported worldwide. A 46-year-old healthy man visited a local clinic for general weakness and hyposmia, and underwent examination with serial endocrinological workup and brain imaging. (68)Gallium-DOTA-TOC positron emission tomography scan was helpful where diagnosis of sellar MRI and inferior petrosal sinus sampling were discordant. Combined transcranial and endoscopic endonasal approach surgery was performed, and a diagnosis of esthesioneuroblastoma was given.